Nonownership Business Models in the Manufacturing Industry: The Role of Uncertainty and the Industrial Internet of Things - Bock, Maximilian; Wiener, Martin (Proceedings of the 39th International Conference on Information Systems (ICIS), 2018)
In a nonownership business model (NOBM), a company maintains product ownership and sells only product performance to its customers. While NOBMs are not an entirely new phenomenon, the digital technologies—such as the Industrial Internet of Things (IIoT)—that facilitate the use of such BMs are relatively new. An increasing number of manufacturing companies are looking into offering nonownership services. However, prior research highlights that, so far, manufacturers have had mixed experiences with servitization strategies including IIoT-based services. Therefore, there is an important theoretical and practical impetus for research on how manufacturers can benefit from NOBMs, and how new technologies help manage the uncertainties associated with such BMs. Drawing on a multiple-case study with three globally operating manufacturers, our study examines the uncertainty upsides and downsides resulting from the adoption of NOBMs, as well as the role of IIoT capabilities in unlocking and mitigating these upsides and downsides, respectively. Preliminary study findings are presented, followed by a discussion of contributions and opportunities for future research.<br
Keywords: Nonownership business models; Servitization; Uncertainty downsides and upsides; Industrial Internet of Things; Manufacturing Industry; Multiple-case study